Height variation of gaps in 150‐km echoes and whole atmosphere community climate model electron densities suggest link to upper hybrid resonance - Lehmacher, Gerald A. (2020)
Radar echoes from the daytime lower F region near the magnetic equator, so-called 150-km echoes, have been puzzling researchers for decades. Neither the mechanisms that generate the enhanced backscatter at very high frequencies (typically 30–50 MHz), the sharp lower cutoff height, the intricate layering with multiple echo layers separated by narrow gaps, nor the modulation of the echoes by short-period gravity waves is well understood. Here we focus on the diurnal variation of the echo layers specifically, certain wide gaps in the vertical structure—which apparently descend in the morning, reach their lowest altitude near local noon, and ascend in the afternoon, sometimes described as necklace structure based on the appearance of the layers in range-time-intensity diagrams. Analyzing high-resolution data obtained with the Jicamarca radar between 2005 and 2017, spanning more than one solar cycle, we find that (a) wide gaps and narrow lines occur in vertically stacked, systematically repeating pattern; (b) the gap heights vary with season and solar cycle; and (c) the gap heights can be associated with specific contours of plasma frequencies or electron densities. The last two findings are supported by simultaneous observations of VIPIR ionosonde reflection heights and by comparison of gap heights with electron density contours obtained with the WACCM-X 2.0 global model. Finally, the wide gaps appear to coincide with the double resonance condition, where the upper hybrid frequency equals integer multiples of the electron gyrofrequency. This may explain why field-aligned plasma irregularities are suppressed and enhanced radar backscatter is not observed inside the gaps.